United States : Financial Sector Assessment Program-Detailed Assessment of Implementation on the IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key findings of the Detailed Assessment of Implementation of the IOSCO (International Organization of Securities Commissions) Objectives and Principles of Securities Regulation on the United States. The United States has large, well-developed, and complex securities and derivatives markets. Postcrisis, the legal mandates of the Securities and Exchange Commission (SEC) and the Commodity Futures Trading Commission (CFTC) have significantly expanded. The level of funding of both the SEC and CFTC is a key challenge affecting their ability to deliver on their mandates in a way that provides confidence to markets and investors. The fragmented structure of equity markets remains a key challenge for the SEC.